A talent transfer lifecycle model in sport - Rea, T. (University of Stirling, 2018)
This thesis focussed on examining the talent transfer experiences as lived by the athletes whom went through transitions. The purpose was to examine why athletes chose to continue in their pursuit of international competition by switching sports as well as understanding how they managed the process and their own unique experiences. Talent transfer is a process occurring when an athlete ceases or reduces their involvement in a sport in which they have invested significant time and concentrates their efforts in a sport that is new to them but involving similar skills. The process comprises of athletes who might be able to perform if fast tracked into other sports with sporting organisations seeing the benefits of this alternative talent identification (TID) system with specific examples of success. The first study (chapter 3) examined the athletes` experiences through the transition of talent transfer. Ten athletes were interviewed: five from a supported talent transfer programme (UK Sport/National Governing Body: NGB); and five that went through the process of their own accord (informally). The purpose of the second study (chapter 4) was to examine the subjective experiences and one athlete`s meaning of the talent transfer process, who moved from judo to cycling and internationally medalled in both. A life history was chosen as the methodology in which to convey the information gathered through the process. The purpose of the third study (chapter 5) was to explore 10 purposeful athletes` experiences of the talent transfer process to understand their unique experiences within a supported NGB programme through unstructured interviews. The results from all three studies are discussed and culminate in a model of the talent transfer process (chapter 6) with limitations and future research directions also discussed. In conclusion, the findings offer a unique examination into athletes` experiences through the Talent Transfer Lifecycle Model. Type: Thesis or Dissertation URI: http://hdl.handle.net/1893/28842